2005
DOI: 10.3354/ame040241
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid uptake of Prochlorococcus spp. in surface waters across the South Atlantic Subtropical Front

Abstract: To test the hypothesis that surface-living Prochlorococcus spp. (Pro) cyanobacteria metabolism declines towards the boundaries of its natural habitat, a latitudinal transect of surface waters was sampled from the centre of the Southern Atlantic Gyre (SAG, 20 to 35°S) to the South Subtropical Frontal Zone (SSFZ, 35 to 45°S). Along this transect, amino acid uptake rates of Pro, Synechococcus spp. (Syn) and an average bacterioplankton cell were determined using 35 S-methionine precursor and flow-cytometry sortin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 26 publications
4
68
1
Order By: Relevance
“…Zubkov and co-workers demonstrated that Prochlorococcus use organic nitrogen compounds, e.g. amino acids (Mary et al, 2008;Zubkov and Tarran, 2005;Zubkov et al, 2003Zubkov et al, , 2004, whilst sulphur uptake from dimethylsulfoniopropionate has also been demonstrated (Vila-Costa et al, 2006). The uptake of glucose by Prochlorococcus has also more recently been suggested by Gómez-Baena et al (2008) as the first example of an organic molecule containing only carbon skeletons, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Zubkov and co-workers demonstrated that Prochlorococcus use organic nitrogen compounds, e.g. amino acids (Mary et al, 2008;Zubkov and Tarran, 2005;Zubkov et al, 2003Zubkov et al, , 2004, whilst sulphur uptake from dimethylsulfoniopropionate has also been demonstrated (Vila-Costa et al, 2006). The uptake of glucose by Prochlorococcus has also more recently been suggested by Gómez-Baena et al (2008) as the first example of an organic molecule containing only carbon skeletons, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to substrate supply, the possible impact of picocyanobacteria (Synechococcus and Prochlorococcus) on TLi:TTi ratios must be considered (Zubkov et al 2000, Zubkov & Tarran 2005. Several species of cyanobacteria have been reported to incorporate leucine but not thymidine (Bern 1985, Kamjunke & Jähnichen 2000, Hietanen et al 2002.…”
Section: Discussionmentioning
confidence: 99%
“…Mixotrophy is known to be common among eukaryotic phytoplankton (i.e. dinoflagellates and ciliates), but significant amino acid uptake was recently also documented in Prochlorococcus, the main prokaryotic primary producers of tropical and subtropical oceans (Zubkov & Tarran 2005). In the year 2000, 2 independent studies documented a widespread ability to utilize light energy among marine bacteria (Béjà et al 2000, Kolber et al 2000.…”
Section: Role Of Aerobic Anoxygenic Phototrophs In the Marine Carbon mentioning
confidence: 99%
“…Fenchel 2001, Karl 2002) and dissolved and particulate organic matter (DOM and POM) is used by prokaryotes that were previously considered to be strictly phototrophic (e.g. Zubkov et al 2003, Zubkov & Tarran 2005, VilaCosta et al 2006, Unrein et al 2007, that chemoautotrophic metabolisms seem to dominate even in well-oxygenated areas of the deep ocean , and that coastal ocean carbon metabolism mediated by bacteria might include lithoheterotrophic metabolisms (Moran & Miller 2007), etc. Considering this, how should we depict the microbial food web?…”
Section: Introductionmentioning
confidence: 99%